Data Processing for IoT in Oil and Gas Refineries - Bagus Satrio Utomo; Hutama A. Bramantyo; Efrilia M. Khusna (Politeknik Negeri Malang, 2022)
This paper summarizes and gives examples of the using of IoT in Industry 4.0, especially in Oil and Gas Refineries. Industry 4.0 and Industrial Internet of Things (IIoT) technologies are driving digitalization driven by software and data solutions in many areas, particularly in industrial automation and manufacturing systems. Global refineries are currently all heavily instrumented, and process regulated in real-time to the millisecond. To meet the ever-increasing needs of operational demands, SCADA, Distributed Control Systems and Programmable Logic Controllers (DCS & PLCs) have grown significantly. On the other hand, certain assets and operations in a refinery are still not being monitored or evaluated in real-time. If an error occurs that causes production to be hampered, the company must bear large losses even though production stops in just a matter of minutes. This is one of the reasons why the oil and gas sector is starting to implement the Internet of Things (IoT). The overall aim of this paper is to give and summarize several papers to provide solutions for a simple process monitoring system that would enable process operators to identify any sources of abnormality quickly and easily in the process. A system is being made so that it can be accessed and transmit data remotely via a computer network and will display conditions in real-time without being limited by distance, space, and time. This will allow all previously disconnected assets and processes to be linked and monitored in real-time in a simpler, cost-effective, and easy-to-implement manner.